2021
DOI: 10.1097/inf.0000000000003069
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Children Born to Pregnant Women With Drug-resistant Tuberculosis Treated With Novel Drugs in Khayelitsha, South Africa: A Report of Five Patients

Abstract: This brief report presents a series of 5 pregnant women treated for rifampicin-resistant tuberculosis with the novel drugs bedaquiline, delamanid, and linezolid as part of an optimized backbone regimen and reviews the outcomes of the children born to them. Although the case series is small, all children had excellent birth outcomes suggesting pregnant women should not be denied access to novel therapies for RR-TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
4
0
2
Order By: Relevance
“…Of the 13 included studies, 6 were animal studies and 7 were human studies. The search performed on PubMed and Embase returned 8 studies (1 animal and 7 human studies)., [24][25][26][27][28][29][30]31 The review performed on the publicly available FDA New Drug Application 021130 Pfizer (Zyvox-linezolid) 2000 to 2021 included 5 animal studies. [19][20][21][22][23] We summarized the linezolid dosage, duration of treatment, disease of interest, sample size, and animal, fetal, and maternal toxicities to assess the safety of linezolid treatment during pregnancy (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 13 included studies, 6 were animal studies and 7 were human studies. The search performed on PubMed and Embase returned 8 studies (1 animal and 7 human studies)., [24][25][26][27][28][29][30]31 The review performed on the publicly available FDA New Drug Application 021130 Pfizer (Zyvox-linezolid) 2000 to 2021 included 5 animal studies. [19][20][21][22][23] We summarized the linezolid dosage, duration of treatment, disease of interest, sample size, and animal, fetal, and maternal toxicities to assess the safety of linezolid treatment during pregnancy (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…A South African study that compared outcomes in pregnant women who did and did not receive bedaquiline found that fetal exposure to bedaquiline in utero was associated with low birthweight (<2500 g), with no other significant differences in infant, pregnancy, or maternal treatment outcomes [ 14 ]. Another small case study from South Africa found successful maternal treatment outcomes and excellent birth outcomes in children born to pregnant women who were receiving bedaquiline, delamanid, and linezolid [ 21 ]. In light of this evidence, in their most recent update to treatment guidelines, WHO now recommends a 9-month, all-oral regimen that includes linezolid, instead of ethionamide, for pregnant women with MDR/RR-TB without documented FQ resistance [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…This evidence gap could also be supplemented by developing and using registries of pregnant women with DR-TB treated with these drugs. 10…”
Section: Discussionmentioning
confidence: 99%